University Autonomy and Performance in Indonesia: An Agency Theory Approach - Ikmah, Siti Fiki; Yulianto, Arief (Educational Management, 2025)
This study investigated how agency costs affected the performance of Indonesian state universities operating under different levels of autonomy—those with Legal Entity Status (PTNBH) and those functioning as Public Service Agencies (PTNBLU). Employing a quantitative explanatory design, the research analyzed secondary data from 2020 to 2023, which included financial statements and Key Performance Indicator (IKU) scores. Agency costs were represented by the Operating Expense Ratio (OER) and Asset Turnover Ratio (ATR). The findings revealed that both OER and ATR significantly influenced university performance in both PTNBH and PTNBLU models. PTNBH institutions appeared more responsive to government goals, as indicated by their higher ATR values. Nonetheless, the additional revenue generated through efficient asset utilization was insufficient to offset their elevated operating expenses. The persistently high OER among PTNBH institutions highlighted the need for organizational restructuring to enhance efficiency. Overall, the study provided empirical support for agency theory within non-profit higher education settings and emphasized the critical role of balancing institutional autonomy with strong accountability mechanisms.